The Ecological Effect of Village and Biopsychosocial Factors Affecting the Quality of Life of Elderly in Surakarta, Central Java - Dwi Tour Kumalasari; Bhisma Murti; Vitri Widyaningsih (Journal of Epidemiology and Public Health, 2020)
Background: Along with the increasing number of the elderly, there are many problems expe